Penerapan Good Agricultural Practises (Gap) Dan Pendapatan Usahatani Kelapa Sawit Swadaya Di Lahan Gambut Pasang Surut Di Kabupaten Indragiri Hilir - Maliza; Rosnita; Dewi, Novia (JURNAL AGRICA, 2025)
The limited availability of suitable land for oil palm cultivation encourages farmers to utilise tidal peatlands. However, tidal peatlands are considered less appropriate for oil palm plants. The utilisation of tidal peatlands for oil palm plantations hurts production, productivity, and income received by farmers if farmers do not apply standardised cultivation techniques. This study aims to analyse the application of independent oil palm cultivation techniques, the amount of income of independent oil palm farmers, and the efficiency level of independent oil palm production on tidal peatlands in Indragiri Hilir Regency. The sampling method used was the Accidental Sampling method with 40 samples. This study was conducted in two sub-districts in Indragiri Hilir Regency, namely Kempas District and Tempuling District, using GAP analysis of oil palm cultivation techniques, analysis of farm income and analysis of production efficiency with stochastic frontier. The results of the study indicate that the application of oil palm cultivation techniques on tidal peatlands has not followed the recommendations set by the Palm Oil Research Centre (PPKS) by the principles of Good Agricultural Practices (GAP). Of the 11 recommended cultivation techniques, only land clearing, weed control, planting patterns, and harvesting were applied 100 per cent. The average production of oil palm on tidal peatlands reached 31,181 kg/year, with a productivity of 10,055 kg/ha/year. The average production cost incurred by farmers was Rp9.530.672/ha/year. The total income of farmers reached Rp19.432.482/ha/year, while the average net income of farmers was Rp.9.901.809/ha/year. All farmers who farm oil palm on tidal peatlands have achieved technical efficiency, but are not yet allocatively and economically efficient.